RESIDU INSEKTISIDA PROFENOFOS DAN λ-CYHALOTHRIN DALAM TANAMAN CABE MERAH KERITING (Capsicum annum L.) DI SEKITAR KOTA PEKANBARU - Sofia Anita; T Abu Hanifah (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2023)
Red chili is always attacked by pests and plant diseases. Because of that, farmers used insecticides in excess to avoid diseases. The study aimed to analyze the concentration of insecticide residues on red chili using Gas Chromatography with Flame Photometric Detector (FPD) and Electron Capture Detector (ECD). The concentration of insecticide residues in the red chili was removed in three ways: no wash (control), and after washing with tap water and warm water. Then, the wastewater after washing was analyzed in terms of phosphate and chloride because they dissolved in water. The concentration of phosphate residue was analyzed using UV-Vis Spectrophotometer and the concentration of chloride was analyzed using the Argentometry titration method (Mohr). The results showed that before washing, all the samples of red chili contained profenofos and λ-cyhalothrin residues. The concentration of profenofos were 0.1264-4.5110 mg/kg and λ-cyhalothrin of 0.3220-0.8782 mg/kg. Both insecticide residues were lower than the Maximum Residue Limits (MRLs). After washing with tap water, the concentration of insecticide residues decreased ranging from 8-26% and 29-43% for warm water. The phosphate concentration in wastewater was in the range of 1.6055-7.8899ppm for tap water and 7.89-18.44 ppm for warm water, while chloride’s concentration was in the range of 0-0.1511ppm and 0.1511-0.3777ppm for tap water and warm water, respectively.